The most common problem facing by the maintenance department: a case study between Universiti Tun Hussein Onn Malaysia (UTHM) and Universiti Teknologi Malaysia (UTM) - Yasin, Mohd Norazam; Mohamad Zin, Rosli; Abdullah, Abd Halid; Mahmad, Muhammad Shafiq; Hasmori, Muhammad Fikri (IOP Publishing, 2017)
From time to time, the maintenance works become more challenging due to construction of new building and also aging of the existing buildings. University buildings without any exception require proper maintenance services to support their function requirements and this can be considered as major responsibilities to be fulfilled by the maintenance department in the universities. Maintenance department specifically will face various kinds of problems in their operation works and thus this might influence the maintenance work operations itself. This study purposely to identify the common problem facing by the maintenance department and also to examine the current status of the maintenance department. In addition, this study would also propose any suitable approach that could be implemented to overcome the problem facing by the maintenance department. To achieve the objectives of this study, a combination of deep literature study and carrying out a survey is necessary. Literature study aimed to obtain deeper information about this study, meanwhile a survey aimed at identifying the common problem facing by the maintenance department and also to provide the information of the maintenance department’s organization. Several methods will be used in analyzing the data obtained through the survey, including Microsoft Office Excel and also using mean index formula. This study has identified three categories of problem in the maintenance department, which are management problems, human resource problem, and technical problems. Following the findings, several solutions being proposed which can be implemented as the solution to the problem facing. These suggestions have the potential to improve the maintenance department work efficiency, thus could help to increase the department productivity